Complete Response and Fatigue Improvement With the Combined Use of Cyclophosphamide and Quercetin in a Patient With Metastatic Bladder Cancer: A Case Report. Issue 5 (February 2016) - Di Lorenzo, Giuseppe; Pagliuca, Martina; Perillo, Teresa; Zarrella, Aquilino; Verde, Antonio; De Placido, Sabino; Buonerba, Carlo
Abstract : Abstract: Bladder cancer is a major cause of cancer-related mortality, with an estimated 74, 000 new cases and 16, 000 deaths in the United States in 2015. In patients with metastatic disease, vinflunine and taxanes are the most widely used chemotherapy agents in the second-line setting after failure of platinum-based treatment. Cyclophosphamide has been used in combination with paclitaxel in urothelial carcinoma of the bladder, but there are no data about the effectiveness of cyclophosphamide administered as a single agent. We here describe the first case of an advanced bladder cancer patient suffering from grade 2 fatigue. He benefited from administration of third-line single-agent metronomic oral cyclophosphamide plus oral doses of quercetin. A complete, prolonged radiologic response according to the RECIST criteria 1.1 was achieved with minimal toxicity and an improvement in fatigue. Further studies are required to assess the potential benefits associated with the combined use of cyclophosphamide plus quercetin in advanced bladder cancer patients.